The era of digital pharmacy. 3D printing - realities and perspectives - Milen Dimitrov; Dilyana Georgieva; Sofiya Ilieva; Valentina Petkova (Pensoft Publishers, 2023)
3D printing is an innovative technology for building three-dimensional objects by laying down successive layers of material under the control of a computer software. It is entering pharmacy mainly because of its revolutionary potential to provide individualized dosage forms that meet the needs of each patient, due to the possibility to produce objects of many different sizes and shapes. An important aspect of personalized 3D tablets is the possibility to include several active substances in one dosage form, which would reduce the daily number of medications and the frequency of their administration and improve patient compliance. Another advantage of 3D printing is the possibility of producing small batches or even individual drugs for each patient. Despite the many advantages, 3D printing has several technological challenges to overcome before it becomes widely applicable in pharmacy. Five basic technologies are currently applied in pharmaceutical practice: powder-based printing, selective laser sintering, stereolithography, extrusion moulding printing, and electrohydrodynamic 3D printing. This article reviewed development, research focus, and prospects of each technology respectively.